The Neglected Pieces of Designing Collective Decision-Making Processes - Khaluf, Yara; Simoens, Pieter; Hamann, Heiko (Frontiers in Robotics and AI, 2019)
Autonomous decision-making is a fundamental requirement for the intelligent behavior of individual agents as well as collective systems. For artificial systems, one of the key design prerequisites is providing the system with the ability to make proper decisions. Current literature on collective artificial systems inspires decision-making mechanisms from natural collective systems, which manage to survive successfully. Nevertheless, most of the approaches focus on voting mechsnsisms. In this paper, we aim to draw attention to the missed pieces for the design of efficient collective decision-making, mainly information processes in its two types of stimuli and options set.